Groundwater Fluctuation Simulation in Pagelaran Landslide, Cianjur, Indonesia - Twin Hosea Widodo Kristyanto; Asriza Asriza; R. Syahputra; Join Wan C. Sigalingging; Tito L. Indra (Badan Geologi, 2020)
Pagelaran is one of area in Southern Part of Cianjur. This area has high susceptibility of landslide. One of landslide in Pagelaran, which happened on December 2014, has destroyed 13 houses and damaged vital road along 200 m. A year later, it started to conduct observation regarding the slope. The research aimed to know the role of groundwater level fluctuation in Pagelaran Landslide. The geometry of slope and its slip surface were determined using Electrical Resistivity Tomography. The actual groundwater level was determined by measuring it from surrounding artesian wells. Parameters angle of friction, cohesion, and unit weight were obtained from laboratory tests toward undisturbed soil samples. These data were used for analyzing the actual slope stability condition. Then it was conducted the simulation of slope stability in accordance with fluctuations of groundwater level. The simulation was done by raising the groundwater level with range of 0.5 m. The results showed that the actual slope stability was in critical condition with the value of safety factor 1.044. It also showed that slope stability waned as rising of groundwater level. The value of safety factor was reduced by an average of 0.034 in each 0.5 m up of groundwater level until it became failure (FS<1) when the groundwater level was 0.95 m above the actual position. Therefore, it can be concluded that the position of groundwater level played a role toward the stability of slope in Pagelaran. The rising 0.5 m of groundwater level position will reduce the slope safety factor by 0.034. The slope will become failure if the position of groundwater level rises by 0.95 meter from the actual position. To prevent the rising of groundwater level in rainy season, which can trigger landslide, it can be attached pipes along the slope body to flow the groundwater through them.